2005
DOI: 10.1186/1477-7819-3-64
|View full text |Cite
|
Sign up to set email alerts
|

Using the intraoperative hand held probe without lymphoscintigraphy or using only dye correlates with higher sensory morbidity following sentinel lymph node biopsy in breast cancer: A review of the literature

Abstract: Because of variations in techniques and time of assessing morbidity, direct comparisons between studies are difficult. Nevertheless at a minimum, a clear trend is present: having the LS images and skin markings to assist during SLNB appears to yield more favorable morbidity outcomes for the patients compared to performing SLNB with only the probe or performing SLNB with dye alone. These results are extremely pertinent, as the main reason for performing SLNB itself in the first place is to achieve reduced morbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…9 months postsurgery), some authors concluded that having lymphoscintigraphy images and skin markings to assist during SLNB yields more favorable morbidity outcomes. 3 Although comparisons among studies are subject to multiple confounding issues, the SenSzi trial missed the opportunity to assess whether lymphoscintigraphy can be of help in reducing morbidity or the operative time and dissection needed for SLN identification in the overall population or subgroups (old age, overweight, and so on). When planar lymphoscintigraphy and skin markings suggest unclassical locations of axillary SLNs (intramammary, interpectoral [Rotter's node], and so on), single-photon emission computed tomography (SPECT)/computed tomography (CT) acquisition is performed.…”
Section: To the Editormentioning
confidence: 99%
“…9 months postsurgery), some authors concluded that having lymphoscintigraphy images and skin markings to assist during SLNB yields more favorable morbidity outcomes. 3 Although comparisons among studies are subject to multiple confounding issues, the SenSzi trial missed the opportunity to assess whether lymphoscintigraphy can be of help in reducing morbidity or the operative time and dissection needed for SLN identification in the overall population or subgroups (old age, overweight, and so on). When planar lymphoscintigraphy and skin markings suggest unclassical locations of axillary SLNs (intramammary, interpectoral [Rotter's node], and so on), single-photon emission computed tomography (SPECT)/computed tomography (CT) acquisition is performed.…”
Section: To the Editormentioning
confidence: 99%
“…[2,3] For SN biopsy, lymphoscintigraphy has the potential to indicate them before surgery [4] and can reduce morbidity relative to that of gamma probing alone. [5,6] Although lymphoscintigraphy using planar images can identify atypical drainage patterns and identify SN sites, it provides limited spatial information because the image is acquired in only two dimensions. Thus, single-photon emission tomography (SPECT) might provide more valuable information about SN locations.…”
Section: Introductionmentioning
confidence: 99%